In-Service Teachers’ Performance Using Guided Inquiry Computer Simulations to Learn Cellular Respiration - Israel Kibirige (Journal of Education Technology, 2023)
Respiration is one of the difficult biology topics, and teachers have challenges effectively teaching it to minimise misconceptions. The aims of this study was to analyse the effect of guided inquiry computer simulations on pre-service teachers' performance. A quasi-experimental design was used in this study. The subject in this study involving 65 in-service teachers, consist of 33 experimental groups taught using guided inquiry computer simulations, and 32 control groups received instructions using traditional chalk-and-talk. Data were collected using the Academic Performance Test and analysed using a T-test to determine the differences between the groups. Analysis of Covariance was used to find out the effect of the intervention. Both groups were pre-tested to gauge their previous knowledge and post-tested to establish changes after the teaching. The results show experimental group surpassed the control group. Also, males and females performance in the experimental group was similar, suggesting that guided inquiry computer simulations favoured both genders. It implies that guided inquiry computer simulations are effective tools to minimise misconceptions regarding cellular respiration. Thus, the researchers recommend using guided inquiry computer simulations in qualitative and quantitative approaches with a large sample of in-service teachers from different geographic regions.